1988
DOI: 10.1152/ajpheart.1988.254.1.h81
|View full text |Cite
|
Sign up to set email alerts
|

Effects of thyroid state on venous compliance and left ventricular performance in rats

Abstract: The cardiovascular system of hypothyroid, normal, and hyperthyroid rats was studied by evaluation of the peripheral venous circulation and left ventricular (LV) systolic and diastolic performance in rats. Cardiac index (CI) and CI during a volume load were measured in open-chest rats. When compared with control, hypothyroid rats showed a decrease in heart rate, aortic pressure, LV systolic pressure, first derivative for LV pressure (LV dP/dt), CI, and CI during a volume load. LV pressure-volume relation was sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
27
0
1

Year Published

1990
1990
2011
2011

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 0 publications
4
27
0
1
Order By: Relevance
“…Rats were allowed to recover for 4 h. Left ventricular dP/dt was obtained from a differentiating circuit in the physiologic recorder (model 2400, Gould, Inc., Cleveland, OH) with the high-frequency filter cutoff set at 100 Hz. In conscious rats 100-150 consecutive beats of LV pressure were recorded directly onto a computer (model AT, IBM Corp., White Plains, NY) and digitized at 1,000 Hz (6,7). An example of an LV pressure recording in a conscious rat is shown in Fig.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Rats were allowed to recover for 4 h. Left ventricular dP/dt was obtained from a differentiating circuit in the physiologic recorder (model 2400, Gould, Inc., Cleveland, OH) with the high-frequency filter cutoff set at 100 Hz. In conscious rats 100-150 consecutive beats of LV pressure were recorded directly onto a computer (model AT, IBM Corp., White Plains, NY) and digitized at 1,000 Hz (6,7). An example of an LV pressure recording in a conscious rat is shown in Fig.…”
Section: Methodsmentioning
confidence: 99%
“…From the recordings ofLV pressures and dP/dt, LV relaxation was determined in untreated diabetic, treated diabetic, and control rats using previously established methods (6,7). Briefly, the decay of LV pressure with time can be closely approximated by the exponential relation: P= PBe + PA, (1) where PB + PA is LV pressure at maximum negative LV dP/dt, PA is LV asymptote pressure, and a is the constant of the exponential relation.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Together, these effects result in a hyperdynamic circulatory state, 12 the overall effect of which is to alter loading conditions on the heart; the increase in total blood volume increases preload while the decrease in systemic vascular resistance reduces afterload. 12 Gay et al 20 demonstrated in experimental studies that ventricular filling pressures are increased in hyperthyroidism and associated with a decrease in venous compliance.…”
Section: Discussionmentioning
confidence: 99%